MAGMATIC EVOLUTION OF THE MELILITITE-CARBONATITE-NEPHELINITE DYKE SERIES OF THE TURIY PENINSULA (KANDALAKSHA BAY, WHITE SEA, RUSSIA) - Ivanikov V.V.; Rukhlov A.S.; Bell K. (My University, 1998)
Major and trace element data are presented from a suite of melilitite–carbonatite–nephelinite dykes, the youngest of three dykes swarms in the Turiy peninsula, Russia. The most primitive dykes consist of olivine melanephelinites and olivine–melilite melanephelinites that contain high-pressure phases (Cr-diopside and low-Ca forsteritic olivine). These dykes approximate the composition of the parental melt, which probably originated by low-degree partial melting of metasomatized peridotite. Least-squares mass-balance calculations and geochemical modelling indicate that differentiation was controlled by fractional crystallization involving olivine, clinopyroxene, melilite, Ti-magnetite, apatite, and perovskite. The calculated modal proportions of the cumulate minerals correspond to some of the rocks seen in alkaline ultramafic plutons elsewhere in the Kola peninsula. Calciocarbonatite dykes, with quenched primary magmatic fabrics, were probably continuously separated by liquid immiscibility from an evolved carbonated nepheline melilitite parent. The conjugate silicate liquid to the carbonatitic melt is a melilite nephelinite. The distribution of LREE, Zr, Hf, Ta, W, Pb, and Cu between the carbonatite and melilite nephelinite is in reasonable agreement with experimental data on element partitioning between alkaline silicate and carbonate melts.